The Effect Of Yellow Pumpkin Flour Substitution On The Quality Of Chicken Meat Balls - Putri, Eneke Suwandi; Elida, Elida; Holinesti, Rahmi; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Meatballs are a food product made from ground meat, mixed with flour, formed into balls the size of marbles or larger and cooked in water until the meatballs float with a chewy texture. Meatballs are one of the processed meat products that are widely consumed by the public because It tastes delicious and is sold at a relatively affordable price. Efforts to increase the use of chicken meat need to be made by processing it into a quality product, namely chicken meatballs. This research aims to determine the effect of pumpkin flour substitution on the quality of chicken meatballs. Data were analyzed using Analysis of Variance (ANOVA), if Fcount > Ftable then continued with the Duncan Test. The results showed that there was a significant influence on the color of chicken meatballs. Meanwhile, shape, aroma, texture and taste did not show a significant influence. The best overall score was the aroma of chicken meat 3.78 (X0); savory taste 3.78 (X0); fine fibrous texture 3.67 (X0 and X3) pumpkin aroma 2.00 (X3), pumpkin taste 1.89 (X3), sweet taste 3.93 (X2 and X3); savory taste 4.00 (X1, X2, and X3); and 3.80 (X3). The best color test results from this research were treatment (X3) with 60% substitution of pumpkin flour.